Systematic variation in North American tree species abundance distributions along macroecological climatic gradients. Issue 5 (27th January 2019) - Matthews, Thomas J.; Sadler, Jon P.; Kubota, Yasuhiro; Woodall, Christopher W.; Pugh, Thomas A. M.
Abstract: Aim: The species abundance distribution (SAD) is a fundamental pattern in macroecology. Understanding how SADs vary spatially, and identifying the variables that drive any change, is important from a theoretical perspective because it enables greater understanding of the factors that underpin the relative abundance of species. However, precise knowledge on how the form of SADs varies across large (continental) scales is limited. Here, we use the shape parameter of the gambin distribution to assess how meta‐community‐scale SAD shape varies spatially as a function of various climatic variables and dataset characteristics. Location: Eastern North America (ENA). Time period: Present day. Major taxa studied: Trees. Methods: Using an extensive continental‐scale dataset of 863, 930 individual trees in plots across ENA sampled using a standardized method, we use a spatial regression framework to examine the effect of temperature and precipitation on the form of the SAD. We also assess whether the prevalence of multimodality in the SAD varies spatially across ENA as a function of temperature and precipitation, in addition to other sample characteristics. Results: We found that temperature, precipitation and species richness can explain two‐thirds of the variation in tree SAD form across ENA. Temperature had the largest effect on SAD shape, and it was found that increasing temperature resulted in more logseries‐like SAD shapes (i.e. SADs with a relatively higher proportion of rarer species). We also found spatial variation in SAD multimodality as a function of temperature and species richness. Main conclusions: Our results indicate that temperature is a key environmental driver governing the form of ENA tree meta‐community‐scale SADs. This finding has implications for our understanding of local‐scale variation in tree abundance and suggests that niche factors and environmental filtering are important in the structuring of ENA tree communities at larger scales.